Youth and Politics in the Argentine Context: Belief, Assessment, Disposition, and Political Practice among Young Students (2010-12) - Kriger, Miriam Elizabeth (2013)
This paper addresses the relationship between youth and politics in Latin America with a focus on the concern in the 1990s with political “apathy” among youth, which was replaced at the start of the new millennium by the “politicisation” of youth. Nevertheless, these trends have not been sufficiently studied to date, rendering the gathering of empirical evidence necessary. In Argentina, youth participation has increased due to the re-politicisation of society, a framework that was developed as a result of the national reconstruction project implemented after the 2001 economic crisis. In connection with these changes, it is necessary to provide empirical evidence to support the attributed relationship between youth and politics to characterise the dimensions of this relationship. We present the results of research (2010-2012) on students (N=273) at seven middle schools in Buenos Aires obtained using a written questionnaire that included items related to the following: a) a belief in and the assessment of politics and politicians and b) dispositions and political participation practices